CONTRIBUIÇÕES PARA COMPREENDER A FORMAÇÃO NA LICENCIATURA E NA DOCÊNCIA - Dias, Marisa Da Silva; Souza, Neusa Maria Marques De (Faculdade de Educação da Universidade Federal de Minas Gerais, 2017)
ABSTRACT: This paper analyzes aspects of the students university and teachers activities based on the principles of historical-cultural and activity theory through teacher training projects, integrating university and schools public. The considerations presented are derived from research results that the authors develop in the public universities in which they work. The data obtained were arranged and analyzed in accordance with the principles of historical-dialectical materialism, epistemological field of historical-cultural theory. From the analysis of social places and the main activity of the subjects, it conclude is that there is need for differentiation of the elements that comprise the universes of meaning of forms of training is required so that the organization of the training process is performed according to specific areas of knowledge. In this way, the actions will be sustainable both for the movement of change of personal sense, as in teaching activities as the subjects in training will develop.

RESUMO: A partir de projetos de formação de professores, integrando universidade e escolas públicas, analisam-se aspectos da atividade do licenciando e do professor, tendo por base os princípios da teoria histórico-cultural e da teoria da atividade. As considerações apresentadas decorrem de resultados de pesquisas que as autoras desenvolvem nas universidades públicas em que atuam. Os dados obtidos foram dispostos e analisados em conformidade com os princípios do materialismo histórico-dialético, campo epistemológico da teoria histórico-cultural. Conclui-se que, a partir dos lugares sociais e da atividade principal em que os sujeitos se encontram, há necessidade da diferenciação dos elementos nos universos de significação de tais modalidades de formação, para que a organização do processo formativo seja intencionalmente definida em conformidade com áreas específicas de conhecimento, de modo que as ações se tornem sustentáveis para o movimento de mudança tanto de sentido quanto da ação docente que os sujeitos em formação virão a desenvolver.
CONTRIBUTIONS TO UNDERSTAND GRADUATION AND TEACHING TRAINING
Keywords: Teacher training; Education degree; Continuing education; Cultural-historical activity theory; Cultural historic theory.; Formação de professores; Licenciatura; Formação continuada; Teoria da atividade; Teoria histórico-cultural.